Clinical and microbiological facets of ventilator associated pneumonia in the main stream with a practical contact - Usman, Shaik Mohammed; James, Pratibha Malini; M, Rashmi (International Journal of Research in Medical Sciences, 2017)
Background: Ventilator-associated pneumonia (VAP), the most apparent infection in ICUs; life threatening, symbolizes an additional healthcare burden. Clinical traits and etiological agents vary. Early diagnosis is captious & apt tactic of quantitative culture is advocated. Regular surveillance is imperative to define strategies. The objective was to conceptualize VAP; put forth our experience of its occurrence, causative bacteria, clinical silhouette and associated variables; and to pattern antimicrobial resistance in ICUs; contributing this data to devise more pertinent approach. Methods: A prospective survey, executed at a tertiary care set up (multidisciplinary ICUs) analysed clinical and microbiological aspects of 120 patients (>48 hours-mechanical ventilation) in congruence with a clinical criteria of pneumonia by standard microbiological means. Cases were keenly observed to assess mortality. Results: Occurrence of VAP was 42.5% with dominance of males (65%) and age group of 41-60 years (Mean ± SD: 42.26 ± 19.53). Late onset type (60.8%) predominated. Principal symptom/sign was fever (82.5%)/crepitation (67.5%). Cases of OP poisoning (21.7%), associated diabetes mellitus (31.7%) were pre-eminent. Gram negative Bacteria (GNB) formed the major etiology (78.6%), cardinal being Acinetobacter baumannii (32.1%) and Pseudomonas aeruginosa (25%). Multi-drug resistant (MDR)-Acinetobacter baumannii, MDR-Pseudomonas aeruginosa, imipenem resistant Klebsiella pneumoniae and Methicillin resistant Staphylococcus aureus (MRSA) were noticed in 66.7%, 35%, 25% and 42.8% of respective isolates. Mortality record was 21.6%. Conclusions: Reliable mode of isolation (quantitative culture), less invasive sampling (ETA) and antibiotic recycling will augment VAP management. Regular intuition into contemporary trends of antimicrobial profile of etiological agents is crucial to avert undesirable consequences.